The effect of aluminum oxide (Al2O3) and cerium oxide (CeO2) on the structural and mechanical properties of yttria Tetragonal Zirconia Polycrystal (Y-TZP) - Golieskardi M.; Satgunam M.; Ragurajan D.; Ansari M.N.M. (Australasian Ceramic Society, 2023)
Cerium; Elastic moduli; Fracture toughness; Mechanical properties; Oxides; Polycrystals; Sintered alumina; Sintering; Vickers hardness; Yttria stabilized zirconia; Yttrium alloys; Zirconia; Aluminum oxides; Cerium oxides; Effect of addition; Sintering behaviors; Sintering temperatures; Structural and mechanical properties; Tetragonal zirconia polycrystal; Yttria stabilized tetragonal zirconia polycrystals; Aluminum